2020
DOI: 10.1186/s13018-020-01598-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel extramedullary technique to guide femoral bone preparation in mobile unicompartmental knee arthroplasty based on tibial cut and overall alignment

Abstract: Background: The mobile Oxford unicompartmental knee arthroplasty (UKA) implant has been widely used with an intramedullary guide for femoral preparation. We modified the femoral guide technique based on the tibial cut first and spacer block technique. This study was performed to determine the radiographic accuracy and early clinical outcomes of the extramedullary method. Methods: We retrospectively evaluated 50 consecutive patients who underwent UKA using the extramedullary technique. An equal number of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
(28 reference statements)
1
11
0
Order By: Relevance
“…Therefore, this method could also be called the extramedullary technique. Our past research showed that UKA performed using this technique can be as reliable and accurate as the conventional technique in terms of the prosthesis position but that it has a shorter operating time, less blood loss, and more rapid recovery without intramedullary interruption [10]. Moreover, the results of the present study showed that this method can improve the bearing movement trajectory, which is another advantage.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Therefore, this method could also be called the extramedullary technique. Our past research showed that UKA performed using this technique can be as reliable and accurate as the conventional technique in terms of the prosthesis position but that it has a shorter operating time, less blood loss, and more rapid recovery without intramedullary interruption [10]. Moreover, the results of the present study showed that this method can improve the bearing movement trajectory, which is another advantage.…”
Section: Discussionsupporting
confidence: 53%
“…In 2020, we introduced a kinematic alignment technique and con rmed that the prothesis position using this method was similar to that using traditional MP devices [10]. The present study was performed to determine whether this technique can improve the bearing movement trajectory.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…A spacer block preferably of 9 mm is inserted with an alignment guide to check the requisite coronal alignment, tibial slope, and the tightness in 5-10°of flexion. It is recommended to use a 9-mm spacer block instead of an 8-mm spacer block as a 9-mm spacer allows the surgeon intraoperative flexibility of ± 1 mm [47]. The thickness is correct when the 9-mm spacer block can slide easily in and out.…”
Section: Horizontal Cutmentioning
confidence: 99%
“…There is ongoing debate regarding the IM rod with respect to its usefulness. [19] In this study, a three-dimensional (3D) model of the femur and IM rods of different lengths were established using computed tomography (CT). The positioning errors for different rod lengths were obtained through nite element analysis, and correlations between the mathematical model of the femur and swing angle of the rods were evaluated.…”
Section: Introductionmentioning
confidence: 99%